Pernikahan dalam Perspektif Masyarakat Bandung - Langgersari Elsari Novianti; Fredrick Dermawan Purba; Afra Hafny Noer; Lenny Kendhawati (Jurnal Online Psikogenesis, 2018)
This study aims to describe (1) relative importance of marriage, (2) desired timing of marriage, and (3) criteria for marriage readiness. Respondents aged between 15 – 30 years old, 558 individuals, not married, residents of Bandung City. The measurement is Criteria for Marriage Readiness Questionnaire (CMRQ) questionnaire designed by Carrol et al. which has been adapted to Bahasa Indonesia. Results showed that respondents perceived (1) marriage is not important/priority for them at the moment, (2) the ideal age for marriage is about 25 years old, because at this age they are mature/ready to marry, have jobs/carrier/income, and have accomplished higher education degree (bachelor/master). Different from previous findings from Carroll, respondents perceived some criteria which need not to be fulfilled before marriage: (1) have enough sexual experience, (2) have kids before marriage, (3) military service, (4) have lived together with lover, (5) premarital intercourse, (6) drinking and smoking. The present study increases understanding of criteria considered by people that needed to be fulfilled before marriage. The fulfillment of these criteria seems to play a role in the age of first marriage of the people in the city of Bandung. Further studies should be done to investigate the cultural values in perceiving marriage by the people of Bandung.